The Role of The Chronic Disease Management Program in Indonesia (PROLANIS) As A Diabetes Mellitus Management Strategy: A Scoping Review - Fadlilah, Siti; Nugroho, Ariyanto; Bistara, Difran Nobel (YCAB Publisher, 2024)
Background:Diabetes Mellitus (DM) is a non-communicable disease with an increasing number of sufferers every year, and its negative impacts require special attention. The Indonesian government has taken steps to manage DM by establishing the PROLANIS program. Objective:This study aims to identify the roles of PROLANIS in treating DM in Indonesia. Methods:This study used a scoping review design. We performed extensive searches in CINAHL Plus, Cochrane Library, Embase, PubMed, and Google Scholar. Based on the search results, we found a total of 280 articles. After a selection process, 27 articles met the criteria for review. The papers were grouped by year, study design, setting, and the role of PROLANIS. Results:According to research results, PROLANIS effectively maintains and reduces several essential aspects of DM patients' health, such as body mass index, fasting blood glucose, and HbA1c levels. PROLANIS also plays a positive role in improving the lipid profiles of DM patients. Furthermore, PROLANIS contributes to increasing self-efficacy, self-acceptance, self-management, adherence to therapy, and overall quality of life. Conclusion:PROLANIS positively affects the management of DM by improving physical health and enhancing the quality of life for patients. Keywords:chronic disease; Diabetes Mellitus; non-communicable diseases; PROLANIS